Results on mass composition of cosmic rays as measured with LOFAR - Corstanje, A.; Buitink, S.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Krampah, G. K.; Mitra, P.; Mulrey, K.; Nelles, Anna; Pandya, H.; Rachen, J. P.; et al. (Proceedings of Science, 2022)
We present an updated analysis of the mass composition of cosmic rays in the energy range of 1016.8 to 1018.3 eV. It is based on measurements with the LOFAR telescope of the depth of shower maximum, Xmax. We review the improvements to the simulation-based reconstruction setup, as well as the selection method to obtain a minimally biased Xmax dataset. Results include estimates of the mean and standard deviation of the Xmax distribution. A statistical analysis at distribution level has been done as well, using a four-component model of light to heavy nuclei. It confirms our previous results showing a significant low-mass fraction in this energy range. The radio technique has advanced enough that multiple observatories are publishing results on Xmax. As the array layouts and methods vary, it is interesting to compare the approaches, in light of the observed differences in the Xmax results. We therefore show additional information on bias tests used in the Xmax reconstruction and sample selection process.
CRIS-Team Scopus Importer:2023-08-15